Design of an Emotion-Focused Painting Training Program and Evaluation of Its Effectiveness on Autism Symptoms in Children with High-Functioning Autism - Khaki Seddigh, Farzaneh; Kashani Vahid, Leila; Vakili, Samira; Hakimiraad, Elham (KMAN Counseling & Psychology Nexus, 2026)
The present study aimed to design an emotion-focused painting training program and evaluate its effectiveness on autism symptoms in children with high-functioning autism. The research method was quasi-experimental, employing a pretest–posttest design with a control group and a two-month follow-up period. The statistical population consisted of children diagnosed with high-functioning autism, aged 10 to 18 years, in Karaj in 2025. From this population, 30 participants were selected through purposive sampling and randomly assigned to an experimental group (n = 15) and a control group (n = 15). The training program was implemented for the experimental group in 10 sessions, each lasting 45 to 60 minutes (two sessions per week). The research instrument included the Gilliam Autism Rating Scale (GARS-3). Data were analyzed using repeated measures analysis of variance with SPSS version 26. The results indicated that the mean scores of autism symptoms in the experimental group significantly decreased compared to the control group at both posttest and follow-up stages (p < .001). Based on the findings, it can be concluded that the emotion-focused painting training program, emphasizing the identification, expression, and regulation of emotions through painting, was effective in reducing autism symptoms in children with high-functioning autism, and this effect remained stable over time. The use of this program as a complementary intervention in rehabilitation centers and special education schools is recommended.